Degeneration in Phosphor-within-Glass Encasers Featuring Disparate Phosphor forms Applied to High-Powered LED - Phan Xuan Le; Nguyen Thi Phuong Loan; Phan Thi Minh Man (Magister Program of Material Science Graduate School of Universitas Sriwijaya, 2026)
For supplanting traditional illuminating diode units (LED) made of silicone, non-organic chroma transmuters featuring significant thermic consistency as well as translucency, including phosphor-within-glass (PWG), are examined in the form of encasers applied to high-powered LED apparatuses. The study herein concerns the influence from disparate phosphor forms featuring different chromas (LuAG, silicate, CASN as well as oxynitride) upon the dependability as well as degeneration for separate PWG encasers in the case of high-powered LED apparatuses. Regarding said goal, one glass constitution was individually blended into every phosphor form before undergoing a sintering process under proper heat levels, creating respective PWGs. The dependability in said PWGs underwent examination via conventional quickened aging experiments. Brightness penalties as well as variances for chroma coordinate results from the PWGs underwent assessment prior as well as posterior to aging. Thermic as well as dampness-generated abatement mechanism underwent assessment as well. The exterior for PWGs with disparate phosphor samples degenerated disparately, likely caused by formational inconsistencies among the glass latticework as well as phosphor form. As such, identifying the consistency for the glass constitution alongside the employed phosphor form proves paramount for guaranteeing prolonged consistencies for encasers applied to LED apparatuses in the market.